A revision of the genus Pelecocera Meigen with the description of the male of pelecocera persiana Kuznetzov from Iran (Diptera: Syrphidae) - Mengual, Ximo; Kazerani, Farzaneh; Talebi, Ali Asghar; Gilasian, Ebrahim (Zootaxa, 2015)
The genus Pelecocera Meigen (Diptera: Syrphidae) is revised. Type material of most species was studied to describe, illustrate and delimit the male of Pelecocera persiana Kuznetzov, recently discovered from Iran. This is the first known specimen of this species since 1914, when the type female was collected. The diagnostic characters of P. persiana are provided, along with an identification key for Pelecocera species. The lectotype of Pelecocera latifrons Loew is designated.